Implementation of AC motor speed control using PID controller in programmable logic controller (PLC) - Nor Athirah, Azmi (2009)
Motor controller is an equipment that been use to determine the movement of an electric motor in a desired way. The speed control of motor is very difficult to be implemented by using conventional control techniques, as it quires a very complex mathematical model. The purpose of this project is to describe the research of PID controller design based on programmable logic controller (PLC) in order to control the speed of the motor. The model of the PLC that has been used in this project is OMRON CJIG-CPU42P where this PLC has a build in loop control that can be made the ladder diagram quite simple using function block in CX-process tools. In this project, the system without controller shows that is an open loop control. Hence, when break is applied there is no feedback for the system to increase the voltage in order for the motor to maintain the desired speed output. Compare by using the PID controller, when the breaking is applied there is a feedback for the system to increase the voltage to get the desired output. Analysis done and it shows that the Proportional-Integral controller with fine tuning is much better performance compare to the Proportional, Proportional-Integral-Derivative controller with and without fine tuning and without controller in the system.